Organisational control in university management : a multiparadigm approach - Kindsiko, Eneli (Emerald Publishing Limited, 2018)
'Organisational Control in University Management: A Multiparadigm Approach' focuses on significant reform and change in large organisations. The book takes as its primary focus the example of management reform at the University of Tartu, Estonia, foregrounding the complexity of change and reform of the management structures at a HE institution. Eneli Kindsiko presents findings that illuminate issues of organisational control in broader institutional contexts,exploring a wide-ranging set of theoretical and practical implications for many institutional sectors in the organisation studies field. The book presents a thorough overview of literature on organisational control, an in-depth methodological approach (with the study building on three core research paradigms: modernist, symbolic and postmodern), and a conceptual framework for addressing the complexities of organisational control in large institutions.
Includes index.
Keywords: Universities and colleges -- Management.; Organizational change.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books